Efektifitas Alat Perangkap (Trapping) Nyamuk Vektor Demam Berdarah Dengue dengan Fermentasi Gula - Endang Puji Astuti; Roy Nusa R.E.S (ASPIRATOR - Journal of Vector-borne Disease Studies, 2011)
Abstracts. Aedes aegypti is the main vector of dengue fever that is still become healthproblem in the world. Various control efforts has been done at several areas throughchemically or naturally control. Developing mosquitoes trapping tool is an alternativemethod to control mosquitoes besides insecticides utilization. This laboratorium researchutilize sugar fermented process to yield CO2 as one of attractan to mosquito. Production ofethanol and CO2 can be yielded from anaerob sugar fermentation proccess (without O2) bykhamir Saccharomyces cerevisiae activities. The trapped mosquitoes was observed up to 48hours exposure, the highest average of mosquito trapped is on solution treatment with yeast1 gram (43.2%) and 40 gr sugar (48.4%). The highest effectivity of trapping tool both insideor outside was on the 14th day. There were declained amount of trapped mosquitos on 16thand 18th days. This laboratorium research has described that trapping tool with sugarfermented solution were effective to control population of dengue vector.